Glutamate-gated chloride channels of Haemonchus contortus restore drug sensitivity to ivermectin resistant Caenorhabditis elegans - Glendinning, S; Buckingham, S; Sattelle, D; Wonnacott, S; Wolstenholme, A (Public Library of Science, 2011)
Anthelmintic resistance is a major problem in livestock farming, especially of small ruminants, but our understanding of it has been limited by the difficulty in carrying out functional genetic studies on parasitic nematodes. An important nematode infecting sheep and goats is Haemonchus contortus; in many parts of the world this species is resistant to almost all the currently available drugs, including ivermectin. It is extremely polymorphic and to date it has proved impossible to relate any sequence polymorphisms to its ivermectin resistance status. Expression of candidate drug-resistance genes in Caenorhabditis elegans could provide a convenient means to study the effects of polymorphisms found in resistant parasites, but may be complicated by differences between the gene families of target and model organisms. We tested this using the glutamate-gated chloride channel (GluCl) gene family, which forms the ivermectin drug target and are candidate resistance genes. We expressed GluCl subunits from C. elegans and H. contortus in a highly resistant triple mutant C. elegans strain (DA1316) under the control of the avr-14 promoter; expression of GFP behind this promoter recapitulated the pattern previously reported for avr-14. Expression of ivermectin-sensitive subunits from both species restored drug sensitivity to transgenic worms, though some quantitative differences were noted between lines. Expression of an ivermectin-insensitive subunit, Hco-GLC-2, had no effect on drug sensitivity. Expression of a previously uncharacterised parasite-specific subunit, Hco-GLC-6, caused the transgenic worms to become ivermectin sensitive, suggesting that this subunit also encodes a GluCl that responds to the drug. These results demonstrate that both orthologous and paralogous subunits from C. elegans and H. contortus are able to rescue the ivermectin sensitivity of mutant C. elegans, though some quantitative differences were observed between transgenic lines in some assays. C. elegans is a suitable system for studying parasitic nematode genes that may be involved in drug resistance.